Prevalence and factors associated with poor umbilical cord care among postpartum mothers in South Western Uganda: a cross sectional study - Brian Mugoya; James K. Tumwine; Emmanuel Ategeka; Timothy Nduhukire; Valence Mfitumukiza; Munezero Tamu; Amito Paula Mary; Christiana Nkiru Okafor; Jane Turyasingura; Kabami Jane; Mandera Immaculate; Alex Tumusiime; et al. (BMC Pediatrics)
Abstract Background Neonatal sepsis is the third leading cause of new born mortality worldwide. An open umbilical cord stamp is a portal of entry for disease-causing pathogens, making new born babies vulnerable to infections and death. Potentially harmful topical substances are still being used for the care of the umbilical cord in rural Ugandan settings which exacerbates risk for infection. Factors influencing poor cord care remain unknown especially in south western Uganda. This study aimed to determine the prevalence and factors associated with poor umbilical cord care in Kabale district, south western Uganda. Methods The cross-sectional study was done at the Young Child Clinic in Kabale regional referral hospital among postpartum mothers with infants aged 6weeks to 6 months of age. Data was collected, entered into excel and exported to Stata version 14 (StataCorp, College Station, Texas, U.S.A) for analysis. We used the exact method to compute the prevalence of poor umbilical cord care and its corresponding confidence intervals. We used multivariable logistic regression analytical technique to determine the factors associated with poor umbilical cord care. Results Of the 428 mothers that were enrolled, 196 (45.8% (95%CI: 41–50.6)) practiced poor umbilical cord care. Mothers applied various substances on umbilical cord including: petroleum jelly, herbs, saliva, charcoal powder, ash and onions. Factors associated with poor umbilical cord care included: (1) Mothers who had attained a primary level education (AOR = 2.67 95%CI: 1.03–6.94) were more likely to practice poor cord care compared to those who had attained a tertiary education. (2) Mothers who got information about cord care from relatives (AOR = 3.12, 95% CI: 2.04–4.77) and friends (AOR = 3.O6, 95%CI: 1.97–4.73) respectively were more likely to practice poor cord care practices compared to those that had got the information from health workers. Conclusion The prevalence of poor umbilical cord care practice is very high. We recommend increased exposure to health education on proper cord care specifically from health workers among mothers especially those with lower levels of education.